Hubungan Pola Asuh Otoriter dan Dating Violence pada Mahasiswa/I di Pekanbaru - Veronica Kharisma Edwy; Zulian Fikry (INDO PUBLISHING, 2025)
Dating violence or dating violence is a form of behavior that is hurtful or abusive towards a partner in a relationship carried out by one of the parties and the victim of this violence feels physically and mentally injured. One factor that triggers dating violence is family history, where the perpetrator who commits violence has witnessed violence perpetrated by their parents. Authoritarian parenting has an impact on adolescent behavior in committing dating violence. Lack of open communication and overt models of aggression can influence adolescents to imitate these patterns in dating relationships. The aim of this research is to determine the relationship between Authoritarian Parenting Patterns and dating violence among students in Pekanbaru with quantitative research methods. The number of samples used in this research was 315 samples using a purposive sampling technique. Based on the results of the Spearman correlation test, it has a sig value. 0.014 < 0.05 which states that Ha is accepted and H0 is rejected. Based on this decision, it was stated that there was a significant relationship between Authoritarian Parenting and Dating Violence. The correlation coefficient figure of 0.138 means that there is a positive correlation. This proves that the higher the level of Authoritarian Parenting, the higher the Dating Violence.